Gender Dynamics of International Labor Migration in the Kurdistan Region of Iraq - Yerevani, Dr. Mosaleh Yerevani; Kaufman, Dr. Eleanor Kaufman; Aghapouri, Dr. Ziyar Aghapouri (Sulaimani Journal for Humanities, 2026)
This research delves into gender dynamics of international labour migration from the global south and global north to the global south, spotlighting various facets of migrants, such as employment, education, skill levels, and their countries of origin. It goes beyond portraying migrants as mere victims and instead examines the pivotal role and standing of immigrant women. Through the lenses of feminist and migration theories, this paper scrutinizes how economic and socio-cultural factors intertwine with the experiences of female migrants in the Kurdistan Region. It explores migration triggers, encompassing discrimination, living and working conditions, as well as the roles, positions, coping mechanisms, and trajectories of movement. As part of the data collection, 24 female migrant workers engaged in domestic service, education, and NGOs were interviewed. The research challenges stereotypical and patriarchal notions, aiming to acknowledge the significance of female foreign workers. Moreover, it sheds light on south-to-south migration, emphasizing the intricate gender dynamics and the contextual intricacies that shape migrant experiences and reactions.